Organic sesame - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Farmers in Burkina Faso have reached another milestone on the organic road. With the support of TROPEX, the organisation for the export of tropical products, more than 3,000 farmers are growing organic sesame. Total production in 1999 2000 was...